A SA-CASSCF and MS-CASPT2 study on the electronic structure of nitrosobenzene and its relation to its dissociation dynamics. - Soto-Martín, Juan; Peláez, Daniel; Otero-Fernández-de-Molina, Juan Carlos (AIP Publishing, 2021)
The photodissociation channels of nitrosobenzene (PhNO) induced by a 255 nm photolytic wavelength have been studied with the complete active space self-consistent (CASSCF) method and the multistate second-order multiconfigurational perturbation theory (MS-CASPT2). It is found that there exists a triplet route for photodissociation of the molecule. The reaction mechanism consists on a complex cascade of nonadiabatic electronic transitions involving triple and double conical intersections as well as intersystem crossing. Several of the relevant states (S2, S4, and S5 states) correspond to double excitations. It is worthy to note that the last step of the photodissociation implies an internal conversion process. The experimentally observed velocity pattern of the NO fragment is a signature of such a conical intersection.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/9875
Keywords: Estructura electrónica; Disociación; SA-CASSCF; MS-CSPT2; Nitrosobenzene; Electronic structure; Dissociation dynamics